Selective molecular sieving in self-Standing porous covalent-Organic-framework membranes - Kandambeth, S.; Biswal, B. P.; Chaudhari, H. D.; Rout, K. C.; Kunjattu, H. S.; Mitra, S.; Karak, S.; Das, A.; Mukherjee, R.; Kharul, U. K.; Banerjee, R. (Advanced Materials, 2017)
Self-standing, flexible, continuous, and crack-free covalent-organic-framework membranes (COMs) are fabricated via a simple, scalable, and highly cost-effective methodology. The COMs show long-term durability, recyclability, and retain their structural integrity in water, organic solvents, and mineral acids. COMs are successfully used in challenging separation applications and recovery of valuable active pharmaceutical ingredients from organic solvents.